Green Roof Retrofit: A Case Study - Shams, Shahriar (International Journal of Integrated Engineering, 2021)
Retrofitting green roofs on existing buildings efficiently reduces building energy consumption, and variation of indoor temperature. Despite such clear benefits, green roof is not widely practiced, probably due to a number of reasons. Different types of green roofs vary from as simple and thin as 5-cm thick grass covering to as complex as a fully designed park with trees, with weight varying from 15 kg/m2 to over 350 kg/m2, and significantly different installation cost. Moreover, the load capacity may be the predominant constraint, and a structural survey may be required to allow the retrofit. In other words, a thorough investigation is needed to examine roof load capacity, identify green roof type, and determine the cost involvement. Therefore, this paper demonstrates a step-wise decision-making process for a green roof retrofit/construction project, through a case study, in terms of accessibility to roof, structural capacity, type of green roof, ease of construction and maintenance and cost involvement, to suit the prevailing conditions of existing building. Within the allowable load capacity and availability in the local market, the study revealed that semi-intensive type of green roof is the cheapest, with installation cost of Brunei 208/m2 and monthly maintenance cost of Brunei 1/m2, compared to ‘modular extensive’ and ‘intensive’ types. The outcomes ae expected to allow policy makers to devise suitable program in Brunei for undertaking green roof retrofit projects to improve energy performances of existing buildings. Although the outcomes cannot be generalized elsewhere, the methodology developed can be applied for investigating specific cases under certain condition and targeting suitable solutions.